A review of absorption properties in silicon-based polymer derived ceramics. Issue 15 (November 2016) - Duan, Wenyan; Yin, Xiaowei; Li, Quan; Schlier, Lorenz; Greil, Peter; Travitzky, Nahum
Abstract: Design and development of advanced materials for electromagnetic applications and bringing these materials into use is one of the most challenging tasks of materials engineering. Silicon-based polymer derived ceramics (PDCs) are natural candidates for these demanding applications due to their very attractive microstructure and properties. Compared with sintered technical ceramics, such as SiC, Si3 N4, Al2 O3 or ZrO2, polymer derived ceramics offer the possibility of flexible plastic-technical processing, for instance by means of injection molding or extrusion without the employment of additional binder systems. The chemical synthesis permits a purposeful optimization of the polymers with respect to workability, ceramic yield and composition by the substitution of different elements in the basic structure as well as the organic side groups. In many cases the microstructure of PDCs characterized by homogeneous distribution of semiconducting or conducting nano-phases in the amorphous matrix. This can lead to the good microwave absorbing properties. Thus, those materials may not only satisfy the impedance matching but also rapidly attenuate electromagnetic waves. The absorption properties of PDCs can be easily tailored by the design of the molecular precursor, changes in morphology, and volume fraction of the filler particles. Different classes of preceramic polymers are briefly introduced and their absorption properties with adjustable phase compositions and microstructures are presented in this review.